Toward the development of performance-related specification for bio-rejuvenators. (20th June 2018) - Zhou, Fujie; Karki, Pravat; Xie, Shangxian; Yuan, Joshua S.; Sun, Lijun; Lee, Robert; Barborak, Ryan
Highlights: Effect of bio-rejuvenators on low temperature property of binder was investigated. Total fatty acid content is a good performance indicator of bio-rejuvenators. Total fatty acid content correlated better with m -based critical low temperature. It is recommended to control saturated fatty acid (or wax) content within 50%. A framework of performance-related specification for bio-rejuvenators is proposed. Abstract: The use of reclaimed asphalt pavement (RAP) and recycled asphalt shingles (RAS) has many benefits. However, premature cracking has become a serious concern for mixes containing RAP/RAS. Recently, a variety of bio-rejuvenators have been developed to address the premature cracking issue. However, there is no purchasing specification available for bio-rejuvenators. This paper presents the efforts made toward the development of performance-related specification for bio-rejuvenators. A total of eight bio-rejuvenators including seven commercial bio-rejuvenators and one recycled vegetable oil, were evaluated in this study. Their chemical and rheological properties and aging characteristics were measured. In addition, the effectiveness of the eight bio-rejuvenators in improving low temperature property of (recycled) asphalt binders was investigated. Although rheological dynamic viscosity has a fair correlation with the stiffness based low temperature performance grade (PG), the chemical property, total fatty acid content is the preferred performance indicator, because (1) the low temperature PG of recycled asphalt binders is controlled primarily by relaxation property (or m value); and (2) the total fatty acid content has much better correlation with the m-based low temperature PG than the dynamic viscosity. The total fatty acid content was verified by mixing pure fatty acid compounds (palmitic acid, oleic acid, and linoleic acid) with a virgin PG64-22 binder. The identified performance indicator was further confirmed by testing blends of recycled binder/virgin binder/three bio-rejuvenators. Additionally, two field test sections with 30% recycled RAP and bio-rejuvenators were constructed for validation. Laboratory test results of the plant mixes collected from the field clearly validated the effectiveness of total fatty acid content as the performance indicator for bio-rejuvenators. At the end of this paper, a framework of performance-related specification for bio-rejuvenators is proposed. A total of seven aspects of bio-rejuvenators are included: (1) total fatty acid content for bio-rejuvenator classification, (2) saturated fatty acid content for avoiding potential negative effect of wax, (3) flashing point for safety, (4) dynamic viscosity for pumping bio-rejuvenators to the mixing drum, (5) dynamic viscosity ratio of RTFO residue to original rejuvenator for screening out the bio-rejuvenators susceptible to short term aging, (6) RTFO (or TFO) mass loss for avoiding massive loss of volatiles, and (7) specific gravity.